Dietary reference values for potassium. (25th October 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry; Neuhäuser‐Berthold, Monika; Nowicka, Grażyna; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) derives dietary reference values (DRVs) for potassium. The Panel decides to set DRVs on the basis of the relationships between potassium intake and blood pressure and stroke. The Panel considers that randomised controlled trials and an observational cohort study carried out in a European adult population provide evidence that a potassium intake of 3, 500 mg (90 mmol)/day has beneficial effects on blood pressure in adults. Furthermore, there is consistent evidence from observational cohort studies that potassium intakes below 3, 500 mg/day are associated with a higher risk of stroke. Available data cannot be used to determine the average requirement of potassium but can be used as a basis for deriving an adequate intake (AI). A potassium intake of 3, 500 mg/day is considered adequate for the adult population and an AI of 3, 500 mg/day for adult men and women is proposed. For infants and children, the AIs are extrapolated from the AI for adults by isometric scaling and including a growth factor. An AI of 750 mg (19 mmol)/day is set for infants aged 7–11 months. For children, AIs from 800 mg (20 mmol)/day (1–3 years old) to 3, 500 mg/day (15–17 years old) are set. Considering that the daily accretion rate of potassium in fetal and maternal tissues can be met by the adaptive changes which maintain potassium homeostasis during pregnancy, the AI set for adults applies to pregnant women. For lactating women, the amount of potassium needed to compensate for the losses of potassium through breast milk is estimated and an AI of 4, 000 mg (102 mmol)/day is proposed. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/wol1/doi/10.2903/sp.efsa.2016.EN-1095/abstract